The Influence of Digital Advertising, SEO, and Social Media Interaction on Fresh Fish Sales: A Study on Fisheries Agribusiness Startups in East Java - Dimas Bayu Sasongko; Jefri Putri Nugraha (Jurnal Informasi dan Teknologi, 2025)
Digital transformation has changed business operations in various sectors, including fisheries agribusiness, where fisheries startups in East Java utilize digital advertising, SEO, and social media interaction to increase fresh fish sales. This study used a quantitative design with 120 respondents through a Likert scale questionnaire. Multiple regression analysis shows that all three factors have a positive and significant effect on sales performance, with social media interaction being the most dominant. Digital advertising increases awareness and purchase intention through targeted and cost-effective campaigns, SEO strengthens online credibility and visibility, while social media interaction builds consumer trust, engagement, and loyalty. An integrated strategy of all three enables resource optimization, risk mitigation, and short-term sales growth and long-term market resilience. Research limitations include a focus on small-scale startups in East Java, so generalizations need to be made cautiously. Future research should explore more personalized digital strategies, integration of additional platforms, and utilization of advanced data analytics.